2017
DOI: 10.48550/arxiv.1703.10480
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A deep learning classification scheme based on augmented-enhanced features to segment organs at risk on the optic region in brain cancer patients

Abstract: Radiation therapy has emerged as one of the preferred techniques to treat brain cancer patients. During treatment, a very high dose of radiation is delivered to a very narrow area. Prescribed radiation therapy for brain cancer requires precisely defining the target treatment area, as well as delineating vital brain structures which must be spared from radiotoxicity. Nevertheless, delineation task is usually still manually performed, which is inefficient and operator-dependent. Several attempts of automatizing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Dolz et al (2015) used a support vector machine (SVM) algorithm to segment optical nerves on magnetic resonance images (MRI) and a mean DSC of 76% was reported across 15 patients. Their later study (Dolz et al 2017) showed improvements on the optical nerves (DSC 79%) and the chiasm (DSC 83%) via a deep-learning framework combined with hand-crafted features augmentation, though the model was only validated on a small patient cohort (15 patients). Similarly, Ren et al (2018) developed an interleaved 3D-CNNs to segment small-volume structures on H&N CT images, where multi-scale image patches were fed into multi-channel CNNs to yield channel-wise probabilities, which were then interleaved and jointly used to classify voxels.…”
Section: Introductionmentioning
confidence: 99%
“…Dolz et al (2015) used a support vector machine (SVM) algorithm to segment optical nerves on magnetic resonance images (MRI) and a mean DSC of 76% was reported across 15 patients. Their later study (Dolz et al 2017) showed improvements on the optical nerves (DSC 79%) and the chiasm (DSC 83%) via a deep-learning framework combined with hand-crafted features augmentation, though the model was only validated on a small patient cohort (15 patients). Similarly, Ren et al (2018) developed an interleaved 3D-CNNs to segment small-volume structures on H&N CT images, where multi-scale image patches were fed into multi-channel CNNs to yield channel-wise probabilities, which were then interleaved and jointly used to classify voxels.…”
Section: Introductionmentioning
confidence: 99%